The Influence of Teacher-Student Talk Strategy in Reducing Cognitive Anxiety in Facing SNBT Competition - Siti Yuliyanti; Ria Arista Asih; Ermanu Azizul Hakim (Universitas Pendidikan Ganesha, 2025)
The high level of cognitive anxiety experienced by students in facing the National Test-Based Selection (SNBT) is a serious problem because it can interfere with concentration, motivation and learning readiness. This anxiety has a negative impact on students' academic performance and achievement. This study aims to analyse the effectiveness of the Teacher-student Talk (TST) strategy in reducing students' cognitive anxiety facing SNBT. The research subjects consisted of 62 students who had the highest level of cognitive anxiety, who were selected using a purposive sampling technique. Data collection was carried out through a questionnaire using a Likert scale, then analyzed with the Wilcoxon test using the help of SPSS version 25.00 software. The results showed that there was a significant decrease in the average score of students' cognitive anxiety, from 126.2 (pretest) to 90 (posttest), after being given an intervention in the form of TST. This finding shows that the TST strategy is effective as a counselling approach that can significantly reduce cognitive anxiety. This strategy can bean applicable alternative intervention for teachers and counselors in helping students prepare for academic exams with more calm and confidence.